The microsurgical training programme in Gothenburg, Sweden: early experiences. Issue 3 (4th May 2017) - Oltean, Mihai; Sassu, Paolo; Hellström, Mats; Axelsson, Peter; Ewaldsson, Lars; Nilsson, Anders G.; Axelsson, Michael
Abstract: Objective: Microsurgical techniques are increasingly used in routine surgical practice as well as in biomedical research. The training opportunities at standardised training courses are limited, and no microsurgical training facility or programme existed in Scandinavia before 2013. Methods: A microsurgery laboratory was set up and two different courses were started, aiming separately at biomedical researchers and surgeons. The course for biomedical researchers teaches basic microsurgical skills such as vessel isolation, cannulation, and arterial microvascular suture under magnification. The more advanced course for surgeons focuses on various techniques of microvascular and nerve anastomosis. Both courses use a combination of theory and practice, with emphasis on the practical part, the course for surgeons also includes clinically relevant information. Results: Twelve 5-day courses using both non-living models and exercises on laboratory animals have been conducted and attended by 49 researchers and 44 surgeons. The organisation and the programme of the training courses as well as 'The 4E concept' behind the course (educational curriculum, equipment, ergonomy, and evaluation) are further detailed. Conclusions: We have successfully established the first training laboratory and series of microsurgical training courses in Scandinavia at two different levels. The experience from the first 12 courses shows the need for this type of structured training, and confirms that the microsurgical education curriculums needs to be adapted to participants' prerequisites and expectations, and various difficulty levels should be considered.